Dietary polyglycosylated anthocyanins, the smart option? A comprehensive review on their health benefits and technological applications. Issue 4 (9th May 2022) - He, Jingren; Ye, Shuxin; Correia, Patrícia; Fernandes, Iva; Zhang, Rui; Wu, Muci; Freitas, Victor; Mateus, Nuno; Oliveira, Hélder
Abstract: Over the years, anthocyanins have emerged as one of the most enthralling groups of natural phenolic compounds and more than 700 distinct structures have already been identified, illustrating the exceptional variety spread in nature. The interest raised around anthocyanins goes way beyond their visually appealing colors and their acknowledged structural and biological properties have fueled intensive research toward their application in different contexts. However, the high susceptibility of monoglycosylated anthocyanins to degradation under certain external conditions might compromise their application. In that regard, polyglycosylated anthocyanins (PGA) might offer an alternative to overcome this issue, owing to their peculiar structure and consequent less predisposition to degradation. The most recent scientific and technological findings concerning PGA and their food sources are thoroughly described and discussed in this comprehensive review. Different issues, including their physical–chemical characteristics, consumption, bioavailability, and biological relevance in the context of different pathologies, are covered in detail, along with the most relevant prospective technological applications. Due to their complex structure and acyl groups, most of the PGA exhibit an overall higher stability than the monoglycosylated ones. Their versatility allows them to act in a wide range of pathologies, either by acting directly in molecular pathways or by modulating the disease environment attributing an added value to their food sources. Their recent usage for technological applications has also been particularly successful in different industry fields including food and smart packaging or in solar energy production systems. Altogether, this review aims to put into perspective the current state and future research on PGA and their food sources.